Blocking Interleukin-1 Beta Reduces the Evolution of Thoracic Aortic Dissection in a Rodent Model. (December 2020) - Guo, Ling-Ling; Wu, Meng-Tao; Zhang, Li-Wei; Chu, Yong-Xin; Tian, Peng; Jing, Zai-Ping; Li, Jia-Si; Sun, Yu-Dong; Yeung, Kak K.; Zhang, Lei
Abstract : Objective: Thoracic aortic dissection (TAD) is associated with matrix changes, biochemical changes, and inflammatory markers like interleukin-1 beta (IL-1β). However, the exact mechanism remains unknown. This study aimed to investigate the role of IL-1β, matrix metalloproteinase (MMP)-2, MMP-9, smooth muscle cell apoptosis, and elastic fibre fracture in the development of TAD in a rat model. Methods: The TAD rat model was induced by β-aminopropionitrile (BAPN). TAD was investigated in 112 male Sprague–Dawley rats, which were equally divided into four groups of 28 rats (Control, BAPN, BAPN + IL-1β, and BAPN + IL-1β antibody). Systolic blood pressure, survival, and the development of TAD were measured after six weeks. Expression of IL-1β, MMP-2, and MMP-9 was measured by Western blot. Apoptosis, aortic elastin concentration, and biomechanical characteristics were measured by the TdT mediated dUTP nick end labelling assay, Victoria blue staining, and in vitro testing. Results: During six weeks, the mortality was 0% (0/28) in the control group, 53.6% (15/28) in the BAPN group ( p  < .001 compared with the control group), 75.0% (21/28) in the BAPN + IL-1β group ( p  = .007 compared with the BAPN group), and 35.7% (10/28) in the BAPN + IL-1β antibody group ( p  = .023 compared with BAPN group and p  < .001 compared with the BAPN + IL-1β group). IL-1β treatment deteriorates BAPN induced mortality and aneurysm expansion, which were attenuated by anti-IL-1β treatment. In BAPN + IL-1β group, stress and strain parameters were decreased by 13.5%–53.5% and elastin content was decreased by 14%, and IL-1β, MMP-2, and MMP-9 were expressed higher by 117%, 108%, and 75% when compared with the rats in the BAPN group. Contrarily, in the BAPN + IL-1β antibody group, the above changes could be completely (strain, elastin content, and expression of MMP-2) or partly (elasticity modulus, stress, and expression of MMP-9) blocked by anti-IL-1β treatment. Conclusion: IL-1β plays a critical role in TAD formation by altering the expression of MMP-2 and MMP-9, degrading the aortic wall matrix, causing elastic fibre rupture, and changing the stress or strain of the aortic wall. Anti-IL-1β reduces the later effects and could be one of the molecular targets for prognosis and drug treatment of TAD in the future.